Ballad of the bullet : gangs, drill music, and the power of online infamy - Stuart, Forrest (Princeton University Press, 2020)
"Drawing on two years of ethnographic fieldwork and over 150 interviews with gang-affiliated youth in the "Taylor Park" neighborhood on Chicago's South Side, Ballad of the Bullet reveals that those coming of age in America's poorest neighborhoods are developing new, creative, and online strategies for making ends meet. Dislocated by the erosion of the crack economy and the splintering of corporatized gangs, these young people exploit the unique affordances of digital social media to capitalize on an emerging online market for urban violence (or, more accurately, a market for the representation of urban violence). In the past, violence functioned primarily as a means of social control, allowing urban youth to compete in illegal street markets and defend the social statuses otherwise denied to them by mainstream society. Today, with the rise of platforms like YouTube, Instagram, and Twitter, violence has become a premier cultural commodity in and of itself. By amassing millions of clicks, views, and followers, these young people convert their online displays of violence into vital offline resources, including cash, housing, drugs, sex, and, for a very select few, a ticket out of poverty"--